2013
DOI: 10.1002/jcla.21577
|View full text |Cite
|
Sign up to set email alerts
|

tcdAAs a Diagnostic Target in a Loop-Mediated Amplification Assay for Detecting ToxigenicClostridium difficile

Abstract: Background The illumigene® (Meridian Bioscience, Inc., Cincinnati, OH) and GeneOhm® (BD Diagnostics, La Jolla, CA) Clostridium difficile assays target the tcdA gene and tcdB gene, respectively. We assessed the use of tcdA as the molecular target in the illumigene® C. difficile loop‐mediated amplification assay in detecting a wide variety of C. difficile strains including those with tcdA deletions. Methods We tested 38 C. difficile strains and 108 patient stool specimens using the illumigene® assay. The GeneOhm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…While some variant C. difficile strains have deletions at the 3' end of the tcdA gene, the 5' portion remains intact for these strains [12]. A recent study confirmed the ability of the Illumigene assay to detect these Toxin A-/B+ strains [13]. The…”
Section: Accepted M Manuscriptmentioning
confidence: 97%
“…While some variant C. difficile strains have deletions at the 3' end of the tcdA gene, the 5' portion remains intact for these strains [12]. A recent study confirmed the ability of the Illumigene assay to detect these Toxin A-/B+ strains [13]. The…”
Section: Accepted M Manuscriptmentioning
confidence: 97%
“…Firstly, the assays are performed in stool containing a large amount of extraneous DNA which may interfere with the detection [ 11 ]. Recent studies however have not shown much cross reactivity [ 19 , 20 ]. Secondly, the mere presence of toxin genes is not proof of toxin expression.…”
Section: Discussionmentioning
confidence: 99%
“…The illumigene C. difficile assay did not detect the remnant fragments of the tcdA gene in any of the RT033 isolates tested, consistent with a deletion in the 5= end region (4, 5). The illumigene C. difficile assay was designed to target a "conserved" region at the 5= end of tcdA present in all known A ϩ B ϩ and A Ϫ B ϩ toxinotypes (13). This was supported by Couturier et al, who reported detection of the tcdA target sequence in A Ϫ B ϩ strains belonging to toxinotypes VIII and X using the illumigene C. difficile assay (13), and in the present study for RT017 (toxinotype VIII) strains which have a truncated tcdA gene retaining only the A1 fragment of the gene (4).…”
mentioning
confidence: 99%
“…The illumigene C. difficile assay was designed to target a "conserved" region at the 5= end of tcdA present in all known A ϩ B ϩ and A Ϫ B ϩ toxinotypes (13). This was supported by Couturier et al, who reported detection of the tcdA target sequence in A Ϫ B ϩ strains belonging to toxinotypes VIII and X using the illumigene C. difficile assay (13), and in the present study for RT017 (toxinotype VIII) strains which have a truncated tcdA gene retaining only the A1 fragment of the gene (4). Other A Ϫ B ϩ ribotypes tested (RT237, RT280, and RT281) that were known to contain a truncated tcdA region (14,15) were not detected by the illumigene C. difficile assay.…”
mentioning
confidence: 99%